Predicting the experience of dentinal caries or restorative dental treatment in adolescents using D1 and D3 visual caries assessments - Nuttall NM, Deery C. (Blackwell Synergy, 2002)
Standardised epidemiological caries assessments used in oral health surveys have been shown to be poor at predicting whether a tooth surface will be treated restoratively when a patient visits a dentist.